2013
DOI: 10.1128/jcm.01440-13
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Genotypes in Piglet Populations in Germany

Abstract: dClostridium difficile was isolated from 147 of 201 (73%) rectal swabs of piglets from 15 farms of Lower Saxony and North Rhine-Westphalia. In 14 farms, 14 to 100% (mean, 78%) of the animals tested were culture positive. The rate of isolation was 68% postpartum, increased to 94% in animals 2 to 14 days of age, and declined to 0% for animals 49 days of age and older. There was no link between isolation and antibiotic treatment or diarrhea of piglets. Strains were assigned to 10 PCR ribotypes, and up to 4 PCR ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
31
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 41 publications
(57 reference statements)
8
31
3
2
Order By: Relevance
“…C. difficile prevalence in piglets aged less than 7 days was 67.2%. This is higher than reported in the United States (29.6%) (6), Slovenia (50.9%) (7), and the Czech Republic (56.7%) (8) and similar to recent reports from Sweden (67.2%) (11) and Germany (73%) (24). Recovery of C. difficile by enrichment culture was significantly better than direct culture on ChromID (52.4% versus 67.2%; P ϭ 0.001), in accordance with studies of human CDI (25).…”
Section: Discussioncontrasting
confidence: 49%
“…C. difficile prevalence in piglets aged less than 7 days was 67.2%. This is higher than reported in the United States (29.6%) (6), Slovenia (50.9%) (7), and the Czech Republic (56.7%) (8) and similar to recent reports from Sweden (67.2%) (11) and Germany (73%) (24). Recovery of C. difficile by enrichment culture was significantly better than direct culture on ChromID (52.4% versus 67.2%; P ϭ 0.001), in accordance with studies of human CDI (25).…”
Section: Discussioncontrasting
confidence: 49%
“…Knetsch et al (27) found that the PCR ribotypes 078, 126, 033, and 045 are highly related in MLST, as they displayed the same sequence type, ST-11, and contained a deletion (⌬39 bp) in the tcdC gene. Recently published data on the sequence similarities of conserved genes (e.g., gyrA, tcdB, and RNA polymerases) in C. difficile PCR ribotypes showed that strains of ribotypes 033, 078, and 126 were very similar, forming a distinct ribotype group or cluster (19,20,28). Accordingly, the results of the array typing confirm the relatedness of ribotypes assigned to the 033-045-078 group.…”
Section: Discussionsupporting
confidence: 69%
“…A collection of 168 C. difficile reference, field, and type strains representing 48 seq-PCR ribotypes was used to validate the microarraybased assay (Table 1). Eighty-six field strains isolated from animal (calf, piglet, cat, and dog) and human (2 strains) sources were obtained from previous investigations (18)(19)(20) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were considered clonal by MLVA, but in this case the isolates were obtained on two different sampling days and the animals proceeded from different herds. As previously suggested, this finding may indicate either an epidemiological connection between farms (Scheeberg et al, 2013) or slaughterhouse contamination. However, clonal strains were not detected among C. difficile isolates from pig and cattle origins, which indicates that crosscontamination between the two slaughter lines (bovine and porcine) during processing is unlikely.…”
Section: Article In Presssupporting
confidence: 72%